Informal settlements and the care of children 0–3 years of age: a qualitative study - Jegathesan, Thivia; Yousafzai, Aisha; Mantel, Michaela; Sereni, Vittorio; Armstrong, Robert W.; Minhas, Ripudaman Singh (Frontiers in Public Health, 2023)
Background There is a rapid increase in urbanization with a high percentage of people living in poverty in urban informal settlements. These families, including single parents, are requiring accessible and affordable childcare. In Mlolongo, an informal settlement in Machakos County in Nairobi metropolitan area, Kenya, childcare centres, referred to as ‘babycares’ are increasing in number. They are being provided by local community members without attention to standards or quality control. The study objective was to understand parents’, caregivers’ and community elders’ experiences and perceptions in terms of the quality of babycares in Mlolongo to inform the design and implementation of improved early childcare services. Methods Using a community-based participatory research philosophy, a qualitative study including focus group discussions with parents, community elders and babycare centre employees/owners (referred to as caregivers) was conducted in Mlolongo. Results A total of 13 caregivers, 13 parents of children attending babycares, and eight community elders participated in the focus groups. Overall, community elders, parents and caregivers felt that the babycares were not providing an appropriate quality of childcare. The reported issues included lack of training and resources for caregivers, miscommunication between parents and caregivers on expectations and inappropriate child to caregiver ratio. Conclusion The deficiencies identified by respondents indicate a need for improved quality of affordable childcare to support early child development in these settings. Efforts need to be invested in defining effective models of early childcare that can meet the expectations and needs of parents and caregivers and address the major challenges in childcare quality identified in this study.